2017
DOI: 10.2147/opth.s144344
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and visual field changes in normal-tension glaucoma patients treated using either unoprostone or latanoprost: a prospective comparative study

Abstract: PurposeWe conducted a prospective study in patients with normal-tension glaucoma (NTG) who received either isopropyl unoprostone or latanoprost. We compared the drugs in terms of their effects on intraocular pressure (IOP) and visual field loss progression over a 3-year period.Study designProspective, randomized controlled study.MethodsWe enrolled 48 patients with newly diagnosed NTG at Kanazawa University Hospital. Eligible patients were randomly allocated (1:1) to receive either unoprostone or latanoprost op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Sector analysis of TD has been reported to be effective in the evaluation of visual fields in glaucoma. 14,15,[18][19][20] In this study, there were no significant changes in MD and PSD values before and after ptosis surgery. However, in the sector analysis of TD values, while there were no significant changes in inferior TD values, there was a significant improvement in superior TD values.…”
Section: Discussionmentioning
confidence: 50%
“…Sector analysis of TD has been reported to be effective in the evaluation of visual fields in glaucoma. 14,15,[18][19][20] In this study, there were no significant changes in MD and PSD values before and after ptosis surgery. However, in the sector analysis of TD values, while there were no significant changes in inferior TD values, there was a significant improvement in superior TD values.…”
Section: Discussionmentioning
confidence: 50%
“…Latanoprost is comparable to other prostaglandin analogues in efficacy and indeed, a multicentre randomised interventional study of 411 patients showed latanoprost had a similar reduction in IOP compared with bimatoprost or travoprost. 13 In addition, latanoprost causes a greater reduction in IOP compared with unoprostone 14,15 or tafluprost. 16 Although a study has shown bimatoprost to be slightly more efficacious in lowering IOP, the same study also reported that latanoprost caused less conjunctival hyperaemia compared with bimatoprost.…”
Section: European Ophthalmic Reviewmentioning
confidence: 99%